Can we slow the progression of chronic kidney disease? - Wühl, Elke; Schaefer, Franz (Current opinion in pediatrics, 2010)
Purpose of review - Childhood chronic kidney disease usually progresses towards end-stage renal failure once a critical impairment of renal function has occurred. This process is largely independent of the underlying renal disease. Recent clinical trials have provided evidence that the progressive course of chronic kidney disease can be slowed substantially by pharmacological intervention. - Recent findings - Hypertension and proteinuria are the most important independent risk factors for renal disease progression in both adult and pediatric nephropathies. Pharmacological blockade of the renin-angiotensin system provides efficient control of blood pressure and proteinuria, and superior long-term renoprotection compared with other antihypertensive agents. Recent pediatric evidence supports the renoprotective efficacy of tight blood pressure control aiming for the low-normal range. In addition, promising preliminary findings suggest an additional renoprotective potential by correction of metabolic acidosis and hyperuricemia and by administration of antiproliferative and antioxidative drugs. - Summary - Pharmacological renoprotection currently focuses on antihypertensive and antiproteinuric treatment by blockade of the renin-angiotensin system. Intensified blood pressure control can improve 5-year renal survival by 35% in children with chronic kidney disease. Additional complementary strategies under current clinical evaluation bear potential to improve renal survival even further.